Pollen Foraging Activity of Stingless Bee (Heterotrigona itama) in Managed Colonies at the Adat Imbo Putui Forest (AIPF), Kampar Regency - Albana F. Akbar; Novia Gesriantuti; Nofripa Herlina; Nuskan Starif; Said F. Tas’ad (Jurnal Biologi Papua, 2025)
Stingless bees are commonly found in Indonesia, either living naturally or managed in cultivation systems. The main factor determining the success of stingless bee farming is the availability and abundance of plants as food sources. This study aimed to determine the number and timing of foraging activities of stingless bees (Heterotrigona itama) for pollen, the influence of environmental factors on the foraging activities of H. itama for pollen, and the types of plants that have the potential to serve as pollen sources. The foraging activity of H. itama was directly observed from 06:00 to 18:00. The environmental parameters measured included temperature, humidity, and light intensity. The survey of potential pollen source plants was conducted around the managed colony boxes and within a 200-meter radius from the colony boxes. The results showed that H. itama foraging activity peaked at 11:00 (bees leaving the nest), 10:00 (bees returning to the nest without carrying pollen), and 11:00 (bees returning with pollen). Spearman correlation analysis indicated that pollen foraging activity was influenced by light intensity. The potential for pollen source plants around the study site was relatively abundant, with 37 plant species identified.